How Private Tertiary Education Website Benefit To Potential Customer - Chooi, Ooi Teik (2007)
This paper is a comphrehensive study on private college websites feature\'s benefits to their potential customers. The study focuses three selected private tertiary education institution websites; identifying their strength and weakness, followed by recommendation on ways for institutions to improve their websites to gain good impression from potential customers, such that they will re-visit the website to get more informations